Governance of zakat distribution based on Maqasid Al-Syariah: study in Selangor zakat board - Md Rejab, Siti Noorbiah; Wahid, Hairunnizam; Yaacob, Salmy Edawati; Abbas, Mohd Saleh; Ismail, Albert Feisal @ Muhd Feisal; Ismail, Maymunah; Abu Bakar, Marina (ResearchTrentz Academy Publishing Education Services, 2022)
Governance in an organization is an important factor in determining the objectives and goals are achieved. Good governance is a responsible, transparent, and fair institution. These principles will ensure the achievement of the goals and objectives of the institution. For zakat institutions, good governance can contribute to the efficiency and effectiveness of zakat funds. Examination and control of various governance mechanisms are important because zakat institutions control large financial resources. Thus, this study will discuss the governance of zakat distribution seen in terms of assistance and schemes given to asnaf based on the Maqasid al-Syariah approach. This study a qualitative method in nature with the acquisition of secondary data through documentation, history, and observation of researchers. The results of the study found that the governance of zakat distribution coincides with the principles of Maqasid al-Syariah. It is also hoped that this study can help zakat institutions in attracting more zakat payers and in turn become a reference for academics and research in the future.